The Construction of Gender Inequality in the Novel Cinta 24 Jam by Andrei Aksana - Pattisina, Vivi Kezia; Latupapua, Falantino Eryk; Sapulette, Viona (Universitas Pattimura, 2022)
This investigation is conducted due to the identification of gender inequality issues in the novel Cinta 24 Jam. This work by Andrei Aksana examines the development of gender inequality. Construction is an endeavor that forges connections among persons or organizations and engenders a reality that is subjectively possessed and experienced. The concept of construction in the novel Cinta 24 Jam pertains to the portrayal of gender discrimination against women as depicted through the characters within the narrative. This study aims to delineate the formation of gender inequality in Andrei Aksana's novel Cinta 24 Jam. The theoretical advantages of this research may enhance the advancement of theories within literary studies. This research yields advantageous outcomes for readers and offers varied viewpoints on the discourse around Indonesian literary works predominantly authored by women, particularly those addressing topics intrinsic to women's experiences. This study employs a descriptive qualitative research methodology. This study's data consists of words, phrases, and sentences pertaining to the construction of gender injustice in the novel Cinta24Jam by Andrei Aksana. The data source for this study is the novel Cinta 24 Jam by Andrei Aksana, published by PT Gramedia Pustaka Utama in September 2005. This study included library and recording approaches for data collection. The analytical technique is outlined as follows: (1) Diligently and systematically reading the novel Cinta24Jam by Andrei Aksana; (2) identifying and categorizing data; (3) documenting all data identification and classification outcomes on data cards; (4) recognizing concerns related to the construction of gender inequality; and (5) formulating conclusions. The researcher employed theory triangulation to verify the data's validity. This research concludes that the gender inequality in the novel Cinta24Jam by Andrei Aksana is portrayed through marginalization, subordination, and violence against women.